Editorial - 'AbdulHamid AbuSulayman (International Institute of Islamic Thought, 1994)
Man’s physical and intellectual life has become too complicated and diversified for a single individual to internalize, however knowledgeable he or she may be. Hence, ijtihad and renewal are no longer a mission reserved exclusively for a mujtahid, ‘alim, or a leader as was traditionally the case a few centuries ago. Historically speaking, more than a hundd years ago, this demanding reality of human life was recognized by the Ottomans. Rather than following the established traditions of placing the responsibilities of legislation in the hands of a grand mujfuhid, a broad committee of ‘ulama, statesmen, and public figures was set up to take charge of codifying the Hanafi school of fiqh (known as the Majalla). It is therefore the responsibility of scientists, ‘ulama, philosophers, and, above all, social scientists to play a significant role in the ongoing movement of Islamic renewal. Yet the intellectual tcnewal of a nation can only be set on foot with a critique of dominant norms, paradigms, and ideals, whether of intrinsic mots or of foreign origins. Indeed, it is through a comprehensive and constructive critical insights that society will be able to develop a new and invigorating worldview. This is the starting point and common denominator shared by most articles of this issue of AJISS. Mona M. Abul-Fadl proposes an extensive and profound analysis of contempomy social theory. Her goal is to illustrate its misrepnasentation of the human venture and to lay the foundation for an Islamic perspective of social theory. Similarly, though on a smaller scale, Abdulwahab al Masseri reflects on the common mts of imperialism, secularism, and the dominant western epistemological outlook. Challenging decaying ideals of other categories, Taha J. al ‘Alwini presents a detailed reformulation on the rights of the accused in a typical Islamic judicial system. By drawing on primary Islamic texts and classical fiqh sources, his work epitomizes that of a contemporary faqih vis-a-vis contemporary issues. Suha Taji-Farouki's article is in contrast With that of al ‘Alwani. Here, a social scientist attempts to deconstruct a moden faqih’s (al Nabhani ...